2013
DOI: 10.4028/www.scientific.net/amr.655-657.2335
|View full text |Cite
|
Sign up to set email alerts
|

Case Study on FMECA and Risk Assessment for the Door System in High Speed Train

Abstract: Based on the FMEA and risk assessment analysis method, authors proposed 25 kinds of failure modes about the door system of high-speed train, conducted a risk assessment from the risk grade and criticality. Four kinds of failure modes are obtained with the highest level of risk and criticality in the door system of high-speed train. They are control failure, communication failure, compensator failure and poor function. Four key components, affecting the door system safety of high-speed train, are identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Due to the limitations of their attributes, they cannot identify a certain fault type. Failure mode and effects analysis (FMEA) is used to evaluate the reliability of high-speed train door system [8]. Bayesian network model using expert system knowledge is developed to diagnose the faults of sliding plug doors [9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the limitations of their attributes, they cannot identify a certain fault type. Failure mode and effects analysis (FMEA) is used to evaluate the reliability of high-speed train door system [8]. Bayesian network model using expert system knowledge is developed to diagnose the faults of sliding plug doors [9].…”
Section: Introductionmentioning
confidence: 99%
“…Pliego and Garcia 13 utilized the Birnbaum and criticality importance measures of fault tree events to perform the prognostic evaluation and diagnosis of point mechanisms. Lu et al 14 identified key causes for a high-speed train door system by analyzing the criticality. Castillo and Grande 15 ranked the most critical causes of railway line accidents by using Bayesian network.…”
Section: Introductionmentioning
confidence: 99%